2012
DOI: 10.1111/j.1095-8649.2012.03358.x
|View full text |Cite
|
Sign up to set email alerts
|

Migratory behaviour of a dominant detritivorous fish Prochilodus lineatus evaluated by multivariate biochemical and pollutant data

Abstract: This paper studies the migration pathways and ranges of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Río de la Plata basin using multivariate analysis of biochemical and pollutant data. Biochemical composition (water, ash, lipids, proteins, carbohydrates, neutral lipids classes and fatty acids), aliphatic hydrocarbons (ALI), polychlorinated biphenyls (PCB), linear alkylbenzenes (LAB) and organochlorine pesticides (OClP) were determined in muscle samples of P. lineatus col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
13
0
3
Order By: Relevance
“…Similarly, fatty acid composition of Buenos Aires P. lineatus was significantly enriched in 18C‐FA (Tukey HSD, P < 0·001), especially 18:1n‐9 and 18:2n‐6, and had lower proportions of 16:1n‐7 and LC‐PUFA (Tukey HSD, P < 0·001), especially 20:4n‐6, 20:5 and 22:6n‐3. A group of 15 Mid‐Paraná individuals (BA MIG) identified as migratory P. lineatus from Buenos Aires based on their length–mass relationship, biochemical composition and pollutant fingerprint (Speranza et al ., ) presented similar lipid, contaminant contents and fatty acid profiles to Buenos Aires P. lineatus [Tables and SI (Supporting Information)]. Excluding these P. lineatus from Mid‐Paraná, the fatty acid composition became indistinguishable from North P. lineatus (18C‐FA: 38·8 ± 7·9%, LC‐PUFA: 16·0 ± 4·7%).…”
Section: Resultsmentioning
confidence: 93%
“…Similarly, fatty acid composition of Buenos Aires P. lineatus was significantly enriched in 18C‐FA (Tukey HSD, P < 0·001), especially 18:1n‐9 and 18:2n‐6, and had lower proportions of 16:1n‐7 and LC‐PUFA (Tukey HSD, P < 0·001), especially 20:4n‐6, 20:5 and 22:6n‐3. A group of 15 Mid‐Paraná individuals (BA MIG) identified as migratory P. lineatus from Buenos Aires based on their length–mass relationship, biochemical composition and pollutant fingerprint (Speranza et al ., ) presented similar lipid, contaminant contents and fatty acid profiles to Buenos Aires P. lineatus [Tables and SI (Supporting Information)]. Excluding these P. lineatus from Mid‐Paraná, the fatty acid composition became indistinguishable from North P. lineatus (18C‐FA: 38·8 ± 7·9%, LC‐PUFA: 16·0 ± 4·7%).…”
Section: Resultsmentioning
confidence: 93%
“…Other methodologies have been used to study migratory and biological aspects of the streaked prochilod, primarily tagging and recapture (Bonetto et al, 1981;Delfino, Baigun, 1985;Sverlij et al, 1993;Espinach Ros et al, 1998) although biochemical methods (Colombo et al, 2011;Speranza et al, 2012) and distribution studies (Bayley, 1973;Stassen et al, 2012) have also been conducted. These studies show brackish use in some specimens, but also suggested the presence of non-migratory fish, especially in the Uruguay River (Bonetto et al, 1981;Delfino, Baigun, 1985;Espinach Ros et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the use of brackish waters and migration distances, other methods of assessment and management should be considered in order to ensure not only the sustainability of the fishery but also the quality of the product for consumption. Management methods should consider connectivity between different points in the basin, paying special attention to brackish use by the species, since this could affect the quality of the meat and affect consumer health (Colombo et al, 2011;Speranza et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Coastal areas of the RdlP, especially the southern (Argentinian) shore, are among the most modified and polluted in the basin because this area contains large industrialised urban conglomerates (Murguía et al 2006;Barletta et al 2010). For example, the concentration of hydrocarbon and polychlorinated biphenyls in detritivorous fish from the southern shore of the RdlP was 1-2 orders of magnitude higher than that of fish from the lower Paraguay River (Speranza et al 2012). Access to the main ports in the RdlP is maintained through dredging, which destroys the physical structure of the benthic ecosystem.…”
Section: Assessment Of Threatsmentioning
confidence: 97%